2015
DOI: 10.1016/j.talanta.2015.04.051
|View full text |Cite
|
Sign up to set email alerts
|

A gas-diffusion flow injection method coupled with online solid–liquid extraction for the determination of ammonium in solid samples

Abstract: A simple, rapid and reliable gas-diffusion flow injection (GD-FI) method for ammonium determination in building materials has been developed. It is based on leaching ammonium from a ground solid sample into an alkaline solution with subsequent ammonia gas generation. Ammonia is then transported in a nitrogen stream to the GD cell of the FI system where it is absorbed into its acceptor solution containing a mixture of the acid-base indicators cresol red and thymol blue. The maximum increase in the absorbance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In the following steps (11)(12)(13), the trapping solution is delivered and "parked" in the holding coil HC-2, by the operation of SP1. Then, a small segment of 40 µL is aspirated through port 4 of the COV, into miniSIA analyzer for fluorimetric quantification.…”
Section: On-line Analytical Proceduresmentioning
confidence: 99%
“…In the following steps (11)(12)(13), the trapping solution is delivered and "parked" in the holding coil HC-2, by the operation of SP1. Then, a small segment of 40 µL is aspirated through port 4 of the COV, into miniSIA analyzer for fluorimetric quantification.…”
Section: On-line Analytical Proceduresmentioning
confidence: 99%
“…19 Timofeeva et al reported an adapted gas-diffusion chamber with a membrane to connect with a flow injection analysis (GD-FIA) system for ammonium determination in building materials. 20 The method is based on the generation of ammonia gas from a solid sample by adding a basic solution. The NH3 gas was carried by N2 gas and dissolved into cresol red and thymol blue as an acceptor solution, and finally, the absorbance of the acceptor solution was detected at 580 nm to quantify the NH4 + .…”
Section: Introductionmentioning
confidence: 99%
“…Methods for determination of NH 4 + are mainly based on spectrophotometry , fluorometry , chemiluminescence , conductometry , potentiometry , and amperometry . DIP is predominantly determined by LC , the most commonly employed technique for pharmaceuticals analysis, and some CE methods .…”
Section: Introductionmentioning
confidence: 99%
“…Medications containing DIP and NH 4 + are popular and widely consumed, and, therefore, a method for the determination of both compounds in a single run is highly desirable. Methods for determination of NH 4 + are mainly based on spectrophotometry [6][7][8], fluorometry [9], chemiluminescence [10,11], conductometry [12,13], potentiometry [14,15], and amperometry [16][17][18][19]. DIP is predominantly determined by LC [20][21][22][23][24], the most commonly employed technique for pharmaceuticals analysis, and some CE methods [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%